From the dark camera to pixels the importance of imaging informational treatment - Dos Santos, Jullia Mendes Pestana [UNESP]; Madio, Telma Campanha de Carvalho [UNESP] (My University, 2019)
The capture or creation of an image can be done by anyone using photography, painting, computer graphics or other artistic or technical form. This work highlights chronological evolution course of the image, and especially the digital scope. Thus, it is observed the importance of informational treatment in the context of the image, making it necessary to know the specificities of each document.
da câmera escura aos pixels a importância do tratamento informacional imagético
Keywords: digital image; evolution of images; processing treatment; technical images